2019
DOI: 10.1128/aac.02214-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Novel Monobactam LYS228 in Murine Models of Carbapenemase-Producing Klebsiella pneumoniae Infection

Abstract: LYS228 has potent antibacterial activity against carbapenem-resistant strains of Enterobacteriaceae. LYS228 was efficacious in neutropenic thigh models established with Klebsiella pneumoniae producing KPC-2 or NDM-1; pretreatment with uranyl nitrate considerably shifted calculated static doses of LYS228. In murine ascending pyelonephritis, LYS228 reduced bacterial burden in kidney, urine, and bladder. The successful treatment of murine infection models established with carbapenem-resistant K. pneumoniae furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In summary, these data demonstrate that variations in the zinc content of commercially available caMHB significantly influence MBL AST and the development of zinc-limited media using EDTA. As evidence of carbapenem efficacy against MBLharboring Enterobacteriaceae in animal infection models continues to mount (14,37,38), a harmonized consensus on the appropriate amount of zinc that culture media should contain will be paramount to optimizing current antimicrobial agents and the development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these data demonstrate that variations in the zinc content of commercially available caMHB significantly influence MBL AST and the development of zinc-limited media using EDTA. As evidence of carbapenem efficacy against MBLharboring Enterobacteriaceae in animal infection models continues to mount (14,37,38), a harmonized consensus on the appropriate amount of zinc that culture media should contain will be paramount to optimizing current antimicrobial agents and the development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…coli and K. pneumoniae strains, including strains expressing KPC and NDM carbapenemases (9, 10). Using this model, it was determined that the predominant PK/pharmacodynamic (PD) parameter associated with antibacterial efficacy of LYS228 was the percentage of the dosing interval that free drug concentrations remained above the MIC of the infecting organism (% T >MIC ) (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…LYS228 is a monobactam antibiotic, which kills bacteria by inhibiting cell wall synthesis through covalent modification of the active-site serine of penicillin binding protein 3 (7, 8). LYS228 is active in vitro and in vivo against Enterobacteriaceae (9, 10). LYS228 is stable to most serine-β-lactamases (SBLs) and all metallo-β-lactamases (MBLs) profiled to date and has demonstrated activity against 271 Enterobacteriaceae strains, including multidrug-resistant isolates (MIC 90 , 1 μg/ml) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Weiss et al confirmed its in vivo efficacy using a neutropenic mice thigh infection model caused by NDM-1 positive K. pneumoniae. In brief, 24-h log 10 CFU/thigh for LYS228 (90 mg/kg q4 h) was significantly lower than that for no drug therapy (Weiss et al, 2019). No study on its antibacterial activity against MBL-producing P. aeruginosa or A. baumannii was found.…”
Section: Lysmentioning
confidence: 90%